Determinants of Exchange Rate Stability in Sudan (1991-2016) - Elfaki, Khalid Eltayeb (International Journal of Economics and Financial Issues, 2018)
Exchange rate is one of the most important indicators of economic growth of a country and its stability has significant impact on international trade. This study aimed to investigate the effects of growth rate of real Gross Domestic Product (GDP), real money supply(M), inflation rate(INF), and trade openness (OP) on exchange rate (EXR) stability in Sudan. For this purpose Autoregressive Distributed Lag Model (ARDL) approach was applied to estimate long run and short run relationship among exchange rate determinants, annual data covering period (1991 -2016) have been analyzed. The results reveal that, there is a long run relationships between exchange rate and its determinants and statistically significant. An increase in growth rate of real GDP leads to stability in EXR. The Coefficient of Error Correction model reveals that exchange rate (EXR) will restore back to its equilibrium with speed of adjustment of 23.2% whenever there is a shock to its equilibrium. Keywords: Exchange Rate, ARDL, Trade Openness. JEL Classifications: F3, F16